Serum Cytokeratin 18 M30 Levels in Chronic Hepatitis B Reflect Both Phase and Histological Activities of Disease - Magdalena Świderska; Jerzy Jaroszewicz; Anna Parfieniuk-Kowerda; Magdalena Rogalska-Płońska; Agnieszka Stawicka; Anatol Panasiuk; Robert Flisiak (Mediators of Inflammation)
Chronic hepatitis B has highly a dynamic course with significant fluctuations of HBV-DNA and ALT impeding assessment of disease activity. New biomarkers of inflammatory versus noninflammatory stages of HBV infection are urgently needed. Cytokeratin 18 epitope M30 (M30 CK-18) is a sensitive marker of cell death. We aimed to investigate an association between serum M30 CK-18 and histological activity and phase of HBV infection. 150 Caucasian patients with HBV-infection were included in the study. Serum M30 CK-18 levels reflected phase of disease, being significantly higher in both HBeAg(+) and HBeAg(−) hepatitis B in comparison to HBsAg(+) carrier groups. The highest serum M30 CK-18 levels were observed in subjects with the most advanced stages of HBV. Moreover, its serum concentrations correlated with both inflammatory activity and fibrosis advancement (ANOVA P<0.001). Importantly, serum M30 CK-18 levels were able to discriminate patients with mild versus moderate-advanced fibrosis (AUC: 0.86) and mild versus active liver inflammation (AUC: 0.79). M30 CK-18 serum concentration has good sensitivity and specificity in discriminating mild versus moderate/severe fibrosis and inflammation even in patients with normal ALT activity. This study suggests M30 CK-18 as a potential noninvasive marker of disease activity and also a marker of phase of persistent HBV infection.